Paternal diabetes programs sex-dependent placental alterations and fetal overgrowth - Fornes, Daiana (2022)
The aim of this study was to evaluate the paternal programming of sex-dependent alterations in fetoplacental growth and placental lipid metabolism regulated by peroxisome proliferator-activated receptor (PPAR) target genes in F1 diabetic males born from F0 pregestational diabetic rats. F1 control and diabetic male rats were mated with control female rats. On day 21 of gestation, F2 male and female fetoplacental growth, placental lipid levels, and protein and mRNA levels of genes involved in lipid metabolism and transport were evaluated. Fetal but not placental weight was increased in the diabetic group. Triglyceride, cholesterol and free fatty acid levels were increased in placentas of male fetuses from the diabetic group. The mRNA levels of Pparα and Pparγ coactivator 1α (Pgc-1α) were increased only in placentas of male fetuses from the diabetic group. Protein levels of PPARα and PGC-1α were decreased only in placentas of male fetuses from the diabetic group. No differences were found in Pparγ mRNA and protein levels in placentas from the diabetic group. The mRNA levels of genes involved in lipid synthesis showed no differences between groups, whereas the mRNA levels of genes involved in lipid oxidation and transport were increased only in placentas of male fetuses from the diabetic group. In conclusion, paternal diabetes programs fetal overgrowth and sex-dependent effects on the regulation of lipid metabolism in the placenta, where only placentas of male fetuses show an increase in lipid accumulation and mRNA expression of enzymes involved in lipid oxidation and transport pathways.